2012
DOI: 10.1097/mnm.0b013e32835674d9
|View full text |Cite
|
Sign up to set email alerts
|

Skin contamination of nuclear medicine technologists

Abstract: Skin contamination can be found in large doses on the skin among nuclear medicine technologists. Single contaminations can result in local skin doses exceeding the yearly dose limit because of the contribution of electrons at shallow depths and should therefore be prevented at any time. The use of a neutral hand soap should generally be preferred during decontamination. A general simplified method is proposed to assess the skin dose after a contamination with 99mTc-labelled radiopharmaceuticals or 18F-fluorode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Therefore, dedicated measurement protocols are needed for the qualitative (radionuclide-specific) and quantitative assessment of contaminated activities over time (98). This assessment, together with the use of tabulated skin dose rate values (35,100) or specific calculation tools such as VARSKIN (101) will enable calculating the cumulated skin doses after a contamination. Two studies have evaluated the impact of contaminations on extremity exposure using a dedicated protocol of on-site detection, precise localization, quantification and dose assessment (98,99).…”
Section: Skin Dose Due To Contaminationmentioning
confidence: 99%
“…Therefore, dedicated measurement protocols are needed for the qualitative (radionuclide-specific) and quantitative assessment of contaminated activities over time (98). This assessment, together with the use of tabulated skin dose rate values (35,100) or specific calculation tools such as VARSKIN (101) will enable calculating the cumulated skin doses after a contamination. Two studies have evaluated the impact of contaminations on extremity exposure using a dedicated protocol of on-site detection, precise localization, quantification and dose assessment (98,99).…”
Section: Skin Dose Due To Contaminationmentioning
confidence: 99%
“…Most radionuclide contamination studies relate to models with thin radioactive layers on the skin [1]. However, droplets of contamination can occur on personal protective equipment (PPE) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the problem of external radiation dose when handling sealed vials and syringes, the manipulation of radiopharmaceuticals also involves contamination risk. A previous contamination survey among nuclear medicine technologists (Covens et al 2012) has shown that skin contamination can contribute substantially to the total localised skin dose of technologists in nuclear medicine. The skin dose limit of 500 mSv y −1 can easily be exceeded as a result of the poor efficacy of decontamination and the electron dose contribution at shallow depths.…”
Section: Introductionmentioning
confidence: 99%